Nutrient management in yard long bean (Vigna unguiculata subsp. Sesquipedalis L.) - Subitha P.R (Department of Agronomy, College of Agriculture, 2013)
A field experiment entitled Nutrient management in yard long bean (Vigna unguiculata subsp. sesquipedalis L.) was conducted at the Instructional Farm attached to the College of Agriculture, Vellayani during 2011-2012 to study the growth, productivity and quality of yard long bean under organic and integrated nutrient management (INM) system and to study the economics of production . The treatments consisted of five nutrient levels and two biofertilizer levels. The experiment was laid out in factorial RBD with three replications. Different nutrient levels showed significant influence on vine length at different growth stages. Application of 20 t FYM along with 10:15:5 kg NPK ha-1 recorded the longest vines at vegetative stage. At flowering and harvesting stage the longest plants were observed with the application of 20 t FYM. Different nutrient levels had significant influence on number of leaves only at flowering stage. Application of 20 t FYM and 10:15:5 kg NPK ha-1 recorded the maximum number of leaves. Inoculation of microbial consortium influenced number of leaves at all the growth stages significantly. At flowering stage combined application of 20 t FYM and 10:15:5 kg NPK ha-1 + PGPR recorded maximum number of leaves. The individual and interaction effect of nutrient levels and bioinoculants were not significant on number of branches per plant. The maximum dry matter was obtained for the treatment receiving 20 t FYM and 10:15:5 kg NPK ha-1. Yield parameters like days to first harvest, days to final harvest and number of pickings were not influenced by different nutrient levels, bioinoculant levels and their interaction. Pods per plant varied significantly due to nutrient levels and bioinoculants. Application of 30 t FYM alone gave maximum number of pods per plant. The same trend was followed for pod yield per plant and pod yield in kg ha-1. Keeping quality of fruits was not significantly influenced by various nutrient levels and bioinoculants. For appearance, overall acceptability and taste of pods the highest score was for the treatment 40 t FYM followed by the application of 20 t FYM ha-1. For colour and texture, application of 20 t FYM + 10:15:5 kg NPK ha-1 obtained highest score. The highest plant nitrogen content was recorded by the application of nutrient level 20 t FYM. Comparing various interaction effects, nitrogen content was higher for the application of 30 t FYM alone. Phosphorus content was unaffected by nutrient levels, bioinoculants and their interaction. Potassium content was found higher with the application of 30 t FYM. Among the various treatment combinations, application of 20 t FYM + 10:15:5 kg NPK ha-1 without biofertilizer recorded highest value for potassium. Nitrogen content in pod was highest with the application of 30 t FYM alone. P and K content in pod were significantly improved by the application of nutrient level 20 t FYM. Comparing various interaction effects, N, P and K content was higher for the treatment 30 t FYM alone. Nutrient uptake by plants varied significantly with respect to various treatments. Plants applied with 20 t FYM recorded the maximum N, P and K uptake. Comparing various interaction effects, application of 30 t FYM alone registered high uptake for N, P and K. With regard to available nutrient status of soil, application of 20 t FYM and 20:30:10 kg NPK ha-1 showed higher availability of N, P and K. Soil treated with bioinoculant recorded higher N, P and K content than without bioinoculant. Economic analysis revealed that among various treatment combinations, application of 30 t FYM alone recorded highest net return which was closely followed by application of 20 t FYM + 10:15:5 kg NPK ha-1 alone. However B: C ratio was highest for 20 t FYM + 10:15:5 kg NPK ha-1 alone which was closely followed by the treatment 30 t FYM alone.